Dynamics in the heme geometry of myoglobin induced by the one-electron reduction. (June 2014) - Choi, Jungkweon; Tojo, Sachiko; Fujitsuka, Mamoru; Majima, Tetsuro
Abstract Purpose: As the conformational change of a protein is intimately related with its function in vivo, the determination of its structure and the understanding of its conformational change occurring in physiological condition is of critical importance. In this regard, we have investigated conformational changes in heme moieties of both folded and unfolded myoglobin (Mb) induced by one-electron reduction. Material and methods: The conformational changes of the heme moiety of folded/unfolded metmyoglobin (metMb) induced by one-electron reduction were investigated using the combination of pulse radiolysis and time-resolved resonance Raman (TR3) spectroscopy. Guanidine-HCl (GdHCl) is used as an electron donor and a denaturant for a protein. Mb solutions containing 0.5 and 2.5 M GdHCl (100 mM phosphate buffer, pH 7.0) were prepared for the measurement of transient absorption and TR3 spectra. Results: Upon reduction, the folded metMb, which had a six-coordinated heme geometry linked with a water molecule as a distal ligand, was structurally relaxed to the deoxymyoblobin (deoxyMb) form with a five-coordination heme geometry without water ligand. Meanwhile, the Raman spectrum of an unfolded metMb was almost identical to those of the unfolded deoxyMb formed by the reduction, indicating that both unfolded metMb and deoxyMb had similar heme geometries. Conclusions: The results provided herein show that upon reduction, the folded metMb with a six-coordinated heme geometry was structurally relaxed to deoxyMb with a five-coordination heme geometry, while both unfolded metMb and deoxyMb had a six-coordinated heme geometry linked with water molecule or histidine as a distal ligand.